Estrogen-Related Receptor Potential Target Genes in Silkworm (Bombyx mori): Insights into Metabolic Regulation - Luyu Hou; Jinxin Wu; Die Liu; Haoran Xu; Hongbo Yao; Yiwen Liang; Qingyou Xia; Ping Lin; Guanwang Shen (Insects)
Estrogen-related receptors (ERRs) are important transcription factors within the nuclear receptor family that regulate cellular energy storage and consumption by binding to estrogen-related receptor response elements (ERREs) on gene promoters. While ERRs’ role in vertebrates is well-studied, their molecular mechanisms in insect metabolism and development remain unclear. This study systematically summarizes the functions of ERRs in insects, focusing on silkworms by analyzing gene functions and comparing databases. ERRE-like elements were identified in the 2000 bp upstream promoter regions of 69 metabolism-related silkworm genes. Furthermore, electrophoretic mobility shift assays (EMSAs) revealed that ERREs within the promoters of 15 genes related to sugar, fat, and protein metabolism specifically bind to ERR. Notably, an ERRE in the promoter of the trehalose transporter 1 gene (BmTret1), crucial for trehalose homeostasis in insect hemolymph, exhibited significantly enhanced activity in ERR-overexpressing cells. These findings suggest that ERR is a potential regulatory factor in silkworm metabolism and refine its metabolic regulatory network. This study highlights the broader and more critical role of ERR in insects than that previously recognized, contributing to a deeper understanding of insect metabolism and its potential applications in related fields.